Transportation: An Electronic Survey of Persons who Are Blind or Have Low Vision. (November 2015) - Crudden, Adele; McDonnall, Michele Capella; Hierholzer, Anne
Introduction: Individuals who are blind or have low vision (hereafter, visually impaired) encounter transportation barriers that impede their full participation in life activities, including transportation. This survey is the first national survey to focus specifically on the transportation issues of persons with visual disabilities. Methods: A transportation survey was developed and disseminated electronically to people who are visually impaired. The first administration, in the fall and winter of 2013, went to persons in a volunteer registry. For the second administration, in early 2014, participants were recruited through electronic postings and e-mails with assistance from consumer groups and professional organizations. The combined useable sample of 492 included individuals with legal blindness ( n = 265), total blindness ( n = 188), and low vision ( n = 39). Results: Participants were likely to have received orientation and mobility (O&M) training, and were confident in their O&M skills. They were also likely to have access to public transportation, to use public transportation to get to work, and to be generally satisfied with how they got to work. Transportation issues were less likely to impact participation in employment than several other life activities. Although most participants had received services from vocational rehabilitation agencies, few said those agencies assisted them in finding transportation to work. Discussion: Although transportation issues affect the lives of persons with visual disabilities, the extent of their impact on employment remains unclear. Survey respondents appear to be using their O&M skills, to be fairly comfortable traveling, and to be generally satisfied with how they travel to work, thus confirming the importance of receiving quality O&M instruction. Implications for practitioners: Service providers should consider evaluating the effect that transportation issues are having on the lifestyles of consumers. Individuals with visual impairments should be encouraged to take advantage of quality O&M instruction so that they can confidently access public transportation systems. More active rehabilitation practitioner participation in assisting consumers locate employment-related transportation is suggested, and evaluating the effect of that assistance would prove helpful.